PENGELOLAAN SUMBERDAYA BUDAYA UNTUK PUBLIK: STUDI KASUS DI UPTD MUSEUM NEGERI PROVINSI PAPUA - Zubair Mas’ud (BALAI ARKEOLOGI PAPUA, 2012)
The presence of cultural resources in Papua UPTD State Museum is an important asset in understanding the culture in Papua. Directed as a means of community identity in Papua through a collection of cultural resources. In facts, the manager of the museum does not provide enough knowledge about relevant information contained in these cultural resources. This study used a qualitative approach with descriptive methods. Based on the results of the study indicate that the management of cultural resources at the State Museum of Papua UPTD not optimally provide knowledge and information to comprehend the culture in Papua which needed by the public. Knowledge or values contained in less cultural resource providing information in accordance with the vision and mission statement by the museum. Therefore, it is necessary to develop the cultural resource management in order to reflect the appreciation of the culture as a people’s identity, in identifying Papua.